Manual de Egipcio Medio - Gracia Zamacona, Carlos (Archaeopress, 2018)
A second revised and updated edition of Carlos Gracia Zamacona's Manual de Egipcio Medio [Handbook of Middle Egyptian]. The book is designed as a primer, written in Spanish, to learn Middle Egyptian (2000-1500 BC) and a guide to read hieroglyphs.